Human Rights Education in Brazil: from the emergence of the theme to the publication of national guidelines (Research, Society and Development, 2021)
The purpose of this text is to carry out an analysis of the trajectory of Human Rights Education in Brazil, from the debates on the theme in the period of re-democratization, to the publication of the National Guidelines. This is a theoretical study of a bibliographic and documentary nature, of a qualitative character. As a result, it is inferred that the inclusion of Human Rights Education in Brazilian education may lead to a more critical and democratic education.